2015
DOI: 10.1038/srep11429
|View full text |Cite
|
Sign up to set email alerts
|

A pathway of nanocrystallite fabrication by photo-assisted growth in pure water

Abstract: We report a new production pathway for a variety of metal oxide nanocrystallites via submerged illumination in water: submerged photosynthesis of crystallites (SPSC). Similar to the growth of green plants by photosynthesis, nanocrystallites shaped as nanoflowers and nanorods are hereby shown to grow at the protruded surfaces via illumination in pure, neutral water. The process is photocatalytic, accompanied with hydroxyl radical generation via water splitting; hydrogen gas is generated in some cases, which ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
47
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 22 publications
(52 citation statements)
references
References 35 publications
0
47
0
Order By: Relevance
“…The incident light-excited electrons then generated holes near the surface. As noted by Jeem et al, 19 when there is water near the surface, holes react with H 2 O molecules to make OH radicals and H + ions. Jeem et al 19 proposed the following whole chemical reactions:…”
Section: -6mentioning
confidence: 99%
See 3 more Smart Citations
“…The incident light-excited electrons then generated holes near the surface. As noted by Jeem et al, 19 when there is water near the surface, holes react with H 2 O molecules to make OH radicals and H + ions. Jeem et al 19 proposed the following whole chemical reactions:…”
Section: -6mentioning
confidence: 99%
“…Recently, Jeem et al discovered a way to produce metal-oxide nanocrystals in ultrapure water via submerged photosynthesis of crystallites (SPSC), 19,20 which built wurtzite ZnO nanorods from Zn 2+ ions dissolved in water and from O 2-ions produced by the photocatalytic effect of H 2 O under UV irradiation. This synthesis process requires no additives, unlike other methods.…”
Section: © 2017 Author(s) All Article Content Except Where Otherwismentioning
confidence: 99%
See 2 more Smart Citations
“…In the pure water environment, the photochemical reaction is considered to contribute to the ZnO nanorod fabrication, as indicated following reaction: . In addition, it was suggested that the formation of the ZnO nanoflowers by SPSC was accompanied by a photoradical reaction via water decomposition, and it was also confirmed that hydrogen is generated during the reaction 19 .…”
Section: Introductionmentioning
confidence: 98%